Vascularisation Pattern of Chronic Pancreatitis Compared with Pancreatic Carcinoma: Results from Contrast-Enhanced Endoscopic Ultrasound - Michael Hocke; Christoph F. Dietrich (International Journal of Inflammation)
Discriminating between focal chronic pancreatitis and pancreatic cancer is always a challenge in clinical medicine. Contrast-enhanced endoscopic ultrasound using Doppler techniques can uniquely reveal different vascularisation patterns in pancreatic tissue alterated by chronic inflammatory processes and even allows a discrimination from pancreatic cancer. This paper will describe the basics of contrast-enhanced high mechanical index endoscopic ultrasound (CEHMI EUS) and contrast enhanced low mechanical index endoscopic ultrasound (CELMI EUS) and explain the pathophysiological differences of the vascularisation of chronic pancreatitis and pancreatic carcinoma. Furthermore it will discuss how to use these techniques in daily clinical practice.